Empowering Housewives through Pipe-Cleaner Flower Craft Training: Strengthening Creative Entrepreneurship and Household Economic Resilience - Rini Hidayati; Nida Nadya Hasan; Elmanizar Elmanizar; Diyah Nur Anggraini (Santoso Academy Network, 2026)
This community service program aimed to empower homemakers in the Pamulang Indah Complex through wire flower-making training integrated with basic entrepreneurship education. The program was initiated in response to the limited technical skills and entrepreneurial literacy among women, despite their potential contribution to supporting household income. The implementation employed a participatory, applied approach comprising preliminary surveys, planning, pre-tests, entrepreneurship counseling, hands-on training sessions, and post-test evaluations. A total of 60 housewives participated in the activity. The evaluation results demonstrated noticeable improvements in participants' understanding of entrepreneurship, development of creativity, and technical skills in producing wire-flower handicrafts. Participants also showed greater self-confidence and enthusiasm in exploring home-based business opportunities after completing the training. Furthermore, they were able to create aesthetically valuable products with market potential independently. The program strengthened household economic resilience, encouraged women's empowerment, and supported the growth of community-based creative economic activities. From a managerial perspective, the findings emphasize the importance of continuous mentoring, product innovation, packaging enhancement, and digital marketing support to ensure the sustainability, competitiveness, and long-term development of small-scale creative businesses within the community.